A Flexible Strategy Towards Thienyl‐, Oxazolyl‐ and Pyridyl‐Fused Fluorenones. Issue 21 (12th June 2013) - Souibgui, Amel; Gaucher, Anne; Marrot, Jérôme; Aloui, Faouzi; Mahuteau‐Betzer, Florence; Ben Hassine, Bechir; Prim, Damien
Abstract: The preparation of new thienyl‐, oxazolyl‐, and pyridyl‐fused benzo[ c ]fluorenones has been developed from a unique and easily available common precursor. Starting from bromotetralone, a short sequence allowed the construction of various heterocycles followed by Suzuki coupling and final acid‐promoted formation of the central cyclopentanone unit. The flexible strategy allowed the selective preparation of fused penta‐ to hepta‐cyclic architectures. Fully aromatic targets have been obtained through the application of an oxidation process. The influence of structural modulations on the photophysical properties are described. Abstract : Thienyl‐, oxazolyl‐ and pyridyl‐fused benzo[ c ]fluorenones were prepared from bromotetralone according to a flexible and short step strategy. The photophysical properties of the products depend on the nature of the fused heterocycle and are crucially influenced by structural modulations.